1989
DOI: 10.1180/minmag.1989.053.370.08
|View full text |Cite
|
Sign up to set email alerts
|

Surface alteration of pentlandite and spectroscopic evidence for secondary violarite formation

Abstract: Synthetic pentlandite surfaces were subjected to oxidation by a range of inorganic oxidants, and the resultant alteration of the surface studied by a range of surface-sensitive spectroscopic techniques. The oxidants used were air during heating to relatively low temperatures (150~ steam, ammonium hydroxide, hydrogen peroxide, and sulphuric acid. Electrochemical oxidation was also undertaken. X-ray photoelectron spectroscopy (XPS), Auger electron spectroscopy (AES), conversion electron M6ssbauer spectroscopy (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
13
0

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 15 publications
4
13
0
Order By: Relevance
“…Equations (3) and (4) are specifically consistent with previous conclusions [11][12][13]. Nickel hexahydrite formation suggests oxidation of nickel sulfide minerals, and based upon its decrease in abundance, from violarite, which is also consistent with published data [14]. The following equation is representative only as iron(II) can be oxidized to iron(III) and either form a sulfate salt at low pH or hydrolyse to goethite at higher pH.…”
Section: Nisupporting
confidence: 89%
“…Equations (3) and (4) are specifically consistent with previous conclusions [11][12][13]. Nickel hexahydrite formation suggests oxidation of nickel sulfide minerals, and based upon its decrease in abundance, from violarite, which is also consistent with published data [14]. The following equation is representative only as iron(II) can be oxidized to iron(III) and either form a sulfate salt at low pH or hydrolyse to goethite at higher pH.…”
Section: Nisupporting
confidence: 89%
“…Our results confirm the previously published conclusions that pyrite is the slowest mineral to oxidize, followed by arsenopyrite (Buckley and Walker 1988;Richardson and Vaughan 1989;Nes-As ( As already observed (Vink 1996;Maruška et al 2000;Ashley et al 2003;Wilson et al 2004), stibnite oxidizes and decomposes quickly and is only rarely observed in oxidation zones. The most frequent secondary phases in the Dúbrava impoundments are oxidation rims around pyrite and arsenopyrite, with relics of the primary sulphides frequently preserved.…”
Section: Discussionsupporting
confidence: 81%
“…Similarly, oxidation processes involving arsenopyrite (FeAsS) are relatively well known (Buckley and Walker 1988;Richardson and Vaughan 1989;Nesbitt et al 1995;Nesbitt and Muir 1998;Corkhill and Vaughan 2009). The weathering products in tailings rich in pyrite or pyrrhotite (Fe 1-x S) have been described in detail (Jambor 1994;Blowes et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Another study, carried out by Richardson and Vaughan (1989) used a variety of oxidizing agents to alter synthetic pentlandite. Their experiments produced quite different results, with iron removed preferentially to nickel from pentlandite, producing a suite of iron oxides and iron hydroxides, with a minor amount of nickel-oxide also forming.…”
Section: Acid or Alkaline Fluids? Conditions For Pentlandite Dissolutionmentioning
confidence: 99%